Osteocytes Serve as a Reservoir for Intracellular Persisting Staphylococcus aureus Due to the Lack of Defense Mechanisms - Garcia-Moreno, Marina; Jordan, Paul M.; Günther, Kerstin; Dau, Therese; Fritzsch, Christian; Vermes, Monika; Schoppa, Astrid; Ignatius, Anita; Wildemann, Britt; Werz, Oliver; Löffler, Bettina; Tuchscherr, Lorena (Frontiers in Microbiology, 2022)
Chronic staphylococcal osteomyelitis can persist for long time periods causing bone destruction. The ability of Staphylococcus aureus to develop chronic infections is linked to its capacity to invade and replicate within osteoblasts and osteocytes and to switch to a dormant phenotype called small colony variants. Recently, osteocytes were described as a main reservoir for this pathogen in bone tissue. However, the mechanisms involved in the persistence of S. aureus within these cells are still unknown. Here, we investigated the interaction between S. aureus and osteoblasts or osteocytes during infection. While osteoblasts are able to induce a strong antimicrobial response and eliminate intracellular S. aureus, osteocytes trigger signals to recruit immune cells and enhance inflammation but fail an efficient antimicrobial activity to clear the bacterial infection. Moreover, we found that extracellular signals from osteocytes enhance intracellular bacterial clearance by osteoblasts. Even though both cell types express Toll-like receptor (TLR) 2, the main TLR responsible for S. aureus detection, only osteoblasts were able to increase TLR2 expression after infection. Additionally, proteomic analysis indicates that reduced intracellular bacterial killing activity in osteocytes is related to low antimicrobial peptide expression. Nevertheless, high levels of lipid mediators and cytokines were secreted by osteocytes suggesting that they can contribute to inflammation.